Cyberbullying and internet addiction in high school students - Sezer Efe, Yağmur; Erdem, Emine; Vural, Birgül (Journal of Dependence, 2021)
Objective: This descriptive study was carried out to determine the relationship between cyberbullying and internet addiction of high school students. Method: The research was carried out on 546 high school students who studying in 9-12 grades. In this study getting the permission of the ethics committee and the institution, the data were collected using the Descriptive Characteristics Form for Adolescents, Cyber Bullying and Aggressiveness on the Internet Scanning Scale (CBAISC) and the Internet Addiction Scale (IAS). Results: Of the high school students, 59.0% were girls, 54.0% were in the 9th grade. Of the students, 32.2% used the internet for 3-5 hours/day on weekdays, 30.2% used for 3-5 hours/day on weekends, 40.1% of them used internet to chat on social networking sites (facebook, twitter, instagram, whatsapp, etc.). The mean scores of the being subjected to cyberbullying and being a cyberbully subscales of CBAISC of students who use internet >7 hours/day on weekdays and weekends were high. A low level significant correlation was found between the total IAS score and the being subjected to cyberbullying and being a cyberbully subscales scores. Conclusion: Informative seminars can be organized for students, families and teachers with the cooperation of health professionals and school administrators/staff about internet addiction, risks to the internet, conscious and healthy use of the internet, cyberbullying. In addition, conducting awareness-raising intervention activities can reduce the occurrence of situations such as internet addiction and cyberbullying / victimization.